Conceptual Metaphor and Creative Literary Individualism - Seyyed AmirHossein Mortezaei; Mahmood Fotoohi Rudmajani (مطالعات زبانی و بلاغی)
Are conceptual metaphors in poetry, the same metaphors we live by? This article wants to answer this question. In order to find an answer, the relation between conceptual metaphor and general culture is explained, and the position of conceptual metaphors in the ordinary cognitive system of society is defined. We introduce repetitive structures which determine application forms of different general conceptual metaphors (cultural). After this introduction, we focus on metaphors in literature. We realized that poets and other people in society have the same cognitive sources. Poet's cognitive system like others is a consequence of society and culture but cultural metaphors appeared differently in his or her poems. Before explaining the quality of its emergence, we describe two main kinds of metaphors (conceptual/image or non-conceptual metaphors) and show their differences. Basically, image metaphors have objective and concrete vehicles and tenors. On the other hand, the tenors of conceptual metaphors are subjective and abstract. In the next part, we draw the borderline of cultural metaphor and poet's innovative metaphor, and passing this line, we introduce methods that make metaphors poetic. There are four main methods that can be used separately or compound: Substitution, organic collectivization, expound, and critical attitude. In the end, we try to understand individuality in art by the form of metaphor application. The relation between the rate of individuality and using conceptual metaphors is based on how different and novel can a metaphor been used in a poem compared with its ordinary usage. Results showed that direct automatic expression and creation respectively could show the maximum and minimum of individuality in art. We choose famous classics poems besides modern contemporary poems to show that the poetical expression of metaphors does not belong to a certain group of poets or a special period of time.